Limits to the Precision of Atomic Lifetime Measurements - Elmar Träbert (Atoms)
The mean lives of certain levels in atoms or not so highly charged ions have been measured with a precision on the order of 0.1%. This is better than most other atomic lifetime measurements, but is still much less precise than many measurements of other entities. Why is it that atomic level lifetime and transition rate measurements are not much more precise?